A educaçao de pessoas jovens e adultos e a cidadania no campo: um olhar sobre o PRONERA no norte do Tocantins. - Pereira, Fabiola Andrade (2008)
The investigation seeks to understand the Education of Young and Adult People as a right of citizenship in the field. The issue that led to the elaboration of this paper consisted in the search of the meanings attributed by settlers to citizenship, which have been guiding their practices and reflections, considering that those perceptions mediate their daily behavior. Based upon the study of PRONERA and of its subproject Education in the field: the richness of its production in Tocantins state, Brazil, as well as in the analysis of the interviews conducted with the settlers in the Settlement Program (PA) Santa Cruz II, in Bico do Papagaio region, Tocantins state, it was possible to reveal the meanings of the life experiences of the involved individuals, concerning a re-conceptualization of rural as field , making to emerge fundamental elements of the constitution process of citizenship in that region. The study of the current literature about the issue has been reinforcing the importance of the social movements in the field and their propositions, as, for instance, PRONERA and, mainly, the Young and Adult People Education policies as a right of citizenship in the field.